Răspuns :
x°y=3xy+3x+3y+2=3(xy+x+y+1)-1=3[x(y+1)+(y+1)]-1=3(x+1)(y+1)-1
n°(n-1)=3(n+1)(n-1+1)-1=3n(n+1)-1
n°(n-1)<17
3n(n+1)-1<17
3n(n+1)<18
n(n+1)<6
n²+n-6<0
(n-2)(n+3)<0
n∈(-3;2)
n∈N => n∈{0;1}
n°(n-1)=3(n+1)(n-1+1)-1=3n(n+1)-1
n°(n-1)<17
3n(n+1)-1<17
3n(n+1)<18
n(n+1)<6
n²+n-6<0
(n-2)(n+3)<0
n∈(-3;2)
n∈N => n∈{0;1}
n ○ (n-1) = 3n(n-1) + 3n + 3(n-1) +2 = 3n² -3n +3n +3n - 3 +2 =
= 3n² +3n -1
n ○ (n-1) < 17 ⇒ 3n² +3n -1 <17 ⇒3(n² +n) < 18|:3 ⇒ n²+n < 6 ⇒
⇒ n(n+1) < 6 ⇒ n ∈ {0, 1}
= 3n² +3n -1
n ○ (n-1) < 17 ⇒ 3n² +3n -1 <17 ⇒3(n² +n) < 18|:3 ⇒ n²+n < 6 ⇒
⇒ n(n+1) < 6 ⇒ n ∈ {0, 1}